KONSUMSI MINUMAN BERALKOHOL DAN KADAR ASAM URAT PADA PRIA DEWASA DI KELURAHAN KOYA KECAMATAN TONDANO SELATAN KABUPATEN MINAHASA - Ana B. Montol; Agnes Rotinsulu (Jurnal GIZIDO, 2014)
Nationally, the prevalence of joint disease (gout arthritis) is 34%. In North Sulawesi, one infour people aged> 15 years suffering from diseases of the joints (gouty arthritis) based onthe diagnosis of health professionals and symptoms. Joint disease and the diagnosis isbased on symptoms found throughout the district / city where the prevalence variesbetween 16% - 34.1%. The highest joint disease in South Minahasa District of 34.1%, orabout one in three, while the city of Bitung is 28% and the lowest in the city of Manado(16.6%) were at one in six people aged> 15 years. While if it is based on the diagnosisonly, the joint disease found in about one in ten people aged> 15 years (11.4%). Thehighest prevalence was found in Bolaang Mongondow that nearly one in four people aged>15 years and lowest in Tomohon, four among a hundred people> 15 years (4%). This studyaims at knowing the relationship with the consumption of alcoholic beverages uric acidlevels in adult males in the village Koya Tondano District South Minahasa regency.This type of research is an observational study with cross sectional design. Number ofsamples 49 were determined by purposive sampling. The measurement of theconsumption of alcoholic drinks and intake of foods high in purine using a food frequencyquestionnaire and qouestionnaire, while the measurement of uric acid levels is done withlaboratory tests. Data analysis using Spearman's rho correlation test.The results obtained by the research sample contained the highest in the age group 41-50years. After analysis of data consumption of alcoholic beverages with high levels of uricacid test analytic correlation Spearman's known the value of the correlation coefficient ofSpearman's rho of 0.284 with a significance level ρ = 0.048 (ρ <0.05), while the analysis ofthe data volume of the alcohol to the uric acid levels using test analytic Spearman'scorrelation coefficient known Spearman's rho correlation of 0.479 with a significance level ρ= 0.00 (ρ <0.01). The conclusion of this research that there is a significant associationbetween the consumption of alcoholic beverages with high levels of uric acid adult males inthe village Koya Tondano District South Minahasa regency.